Urinary tract infections in older adults: associated factors for extended-spectrum beta-lactamase production - Alkan, Sena; Balkan, Ilker Inanc; Surme, Serkan; Bayramlar, Osman Faruk; Kaya, Sibel Yildiz; Karaali, Ridvan; Mete, Bilgul; Aygun, Gokhan; Tabak, Fehmi; Saltoglu, Nese (Frontiers in Microbiology, 2024)
Objective: Urinary tract infections (UTIs) due to extended spectrum beta lactamase (ESBL) producing Escherichia coli and Klebsiella pneumoniae. are among the leading causes of morbidity and mortality in older adults. Identifying associated factors for ESBL production may contribute to more appropriate empirical treatment.This was a prospective observational study. Hospitalized patients of age >65 with community-onset or hospital-acquired upper UTI due to E. coli or Klebsiella pneumoniae was included. A multivariate analysis was performed.Results: A total of 97 patients were included. ESBL prevalence among UTIs with E. coli or Klebsiella pneumoniae was 69.1% (n=67). CRP values at the time of UTI diagnosis were found to be significantly higher in the ESBL-producing group (p=0.004). Multivariate analysis revealed that male gender (OR:2.72, CI:1.02-7.25), prior recurrent UTI (OR:3.14, CI:1.21-8.14), and development of secondary bacteremia (OR:4.95, CI:1.03-23.89) were major asssociated factors for UTI in older adults due to ESBL-producing E. coli and Klebsiella pneumoniae. Severe UTI in older men with a history of recurrent UTI may be a warning to the clinician for ESBL production in the setting of high ESBL prevalence. Carbapenems may be prioritized in the empirical treatment in patients with known risk factors for ESBL.